Value of tumour marker S-100B in melanoma patients: a comparison to 18F-FDG PET and clinical data - Reinhardt, M. J.; Kensy, J.; Frohmann, J. P.; Willkomm, P.; Reinhold, U.; Grünwald, F.; Biersack, H.-J.; Bender, H. (Nuklearmedizin - NuclearMedicine, 2002)
Aim: The S-100B protein is commonly used in the immunohistochemical diagnosis of malignant melanoma and its metastases and has recently been introduced as a tumor marker in peripheral blood, whereas 18F-FDG PET is currently the most sensitive in-vivo imaging method for melanoma staging. Thus, the efficency of serum S-100B and 18F-FDG PET in the detection of metastatic disease in melanoma patients are compared. Methods: Serum S-100B was measured with a commercially available immunoradiometric assay. As part of primary tumour staging whole-body positron emission tomography (PET) with 18F labeled fluorodeoxy-D-glucose (18F-FDG) was performed in 67 patients suffering from cutaneous melanoma with a tumour thickness > 0.75 mm and a Clark-level III-V. Final diagnosis based on histology, morphologic imaging results and/or clinical follow-up after at least six months. Results: No evidence of disease was seen in 43 of 67 patients (64.2%), 11 patients (16.4%) presented with lymph node metastases, 13 patients (19.4%) had one or more distant metastases. Alltogether, 18 of 67 patients showed S-100B values > 0.2 µg/l, including two patients without metastatic disease, 3 of 11 patients with lymph node metastases, and the 13 patients with distant metastases. One patient showed false-positive FDG-uptake in the mediastinum, but presented with S-100B values off curve. Conclusion: Our data indicate that serum S-100B determination might be helpful in identifying melanoma patients with distant metastases. In comparison to 18F-FDG PET, the value of serum S-100B for lymph-node staging is limited.
Keywords: S-100B protein; 18F-FDG PET; malignant melanoma